2018
DOI: 10.15761/csrr.1000112
|View full text |Cite
|
Sign up to set email alerts
|

The role of oral contraceptive pills on increased risk of breast cancer in North West of Iran

Abstract: Introduction: Breast cancer is the most common cancer in women, comprising a third of all cancers in women. Used by millions of women on daily basis, contraceptives are a potential risk in incidence of cancer. This study aimed to investigate the relationship between incidence of cancer and use of contraceptive pills. Materials and methods:This is a retrospective analytical control-case study conducted on 235 breast cancer patients and 235 women in the control group. Data collection tools included a set of ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The other study found the afinity between breast cancer and contraceptive pills use (OR=2.11). The investigation results show that women that utilization preventative pills have more noteworthy requirements for preventive and screening measures [34].…”
Section: Discussionmentioning
confidence: 91%
“…The other study found the afinity between breast cancer and contraceptive pills use (OR=2.11). The investigation results show that women that utilization preventative pills have more noteworthy requirements for preventive and screening measures [34].…”
Section: Discussionmentioning
confidence: 91%